Will Urbanology Recover the Resilience of the Korean Church? - Kim, Enoch J. (International bulletin of mission research, 2024)
This article studies the factors which initially contributed to Korean church growth became burdensome as the society underwent urbanization. Unlike the early Korean churches, the lack of contextual understanding is taking a toll on the growth of today’s urban church. To help urban churches better interact with their context, this article explores some insights from three disciplines of urbanology. When used appropriately, these urban studies can help the Korean church become a partner in the community and share the incarnate and contextually relevant good news with the people.